Strengthening of concrete structures with adhesive bonded reinforcement : design and dimensioning of CFRP laminates and steel plates - Zilch, Konrad, 1944-; Niedermeier, Roland; Finckh, Wolfgang (Berlin : Ernst & Sohn, 2014)
Selected chapters from the German concrete yearbook are now being published in the new English ""Beton-Kalender Series"" for the benefit of an international audience. Since it was founded in 1906, the Ernst & Sohn ""Beton-Kalender"" has been supporting developments in reinforced and prestressed concrete.
4.5.4 Accurate analysis of concrete element between cracks4.5.4.1 Determining the strip forces; 4.5.4.2 Determining the bond strength; 4.5.5 End anchorage analysis; 4.6 Analysis of shear capacity; 4.7 Serviceability limit state; 5 Design of strengthening with near-surface-mounted CFRP strips; 5.1 Principles; 5.2 Verification of flexural strength; 5.3 Bond analysis; 5.4 Shear Force Analyses; 5.5 Fatigue analysis; 5.6 Analyses for the serviceability limit state; 5.7 Detailing; 6 Example 2: Strengthening a beam with near-surface-mounted CFRP strips; 6.1 System; 6.1.1 General; 6.1.2 Loading.
Edition statement from running title area.
Includes bibliographical references (pages 131-143) and index.
Online resource; title from PDF title page (Wiley, viewed July 21, 2014).
Keywords: Structural engineering; Concrete; Fiber reinforced plastics; Laminated plastics; Materials; Polymers; TECHNOLOGY & ENGINEERING -- Civil -- General; Concrete; Structural engineering; Electronic books; Electronic books